A single amino acid substitution in the AAA-type ATPase LRD6-6 activates immune responses but decreases grain quality in rice - Yin, Junjie; Zhang, Cheng; Zhang, Qianyu; Long, Feiyan; Hu, Wen; Zhou, Yi; Mou, Fengying; Zhong, Yufeng; Wu, Bingxiu; Zhu, Min; Zou, Lijuan; Zhu, Xiaobo (Frontiers in Plant Science, 2024)
Plant spotted leaf (spl) mutants are useful to reveal the regulatory mechanisms of immune responses. Thus, in crop plants, their agronomic traits, especially the grain quality are usually ignored. Here, we characterized a rice spl mutant named spl-A (spotted leaf mutant from A814) that shows autoimmunity, broad-spectrum disease resistance and growth deterioration including decreased rice quality. A single nucleotide mutation of C1144T, which leads to change of the 382nd proline to serine, in the gene encoding the ATPases associated with diverse cellular activities (AAA)-type ATPase LRD6-6 is responsible for the phenotype of the spl-A mutant. Mechanistically, this mutation impairs LRD6-6 ATPase activity and disrupts its interaction with endosomal sorting complex required for transport (ESCRT)-III subunits OsSNF7.1/7.2/7.3. And thus, leading to compromise of multivesicular bodies (MVBs)-mediated vesicle trafficking and accumulation of ubiquitinated proteins in both leaves and seeds of spl-A. Therefore, the immune response of spl-A is activated, and the growth and grain quality are deteriorated. Our study identifies a new amino acid residue that important for LRD6-6 and provides new insight into our understanding of how MVBs-mediated vesicle trafficking regulates plant immunity and growth, including grain quality in rice.